The Effect of Problem-Based Learning Using Canva on Senior High School Geography Students' the Concept Understanding of Village and City Spatial Patterns - La Ode Nursalam; Sitti Kasmiati; Tahir Tahir; Ahmad Tarmizi Abdul Karim; Andri Estining Sejati (Universitas Negeri Gorontalo, 2025)
Geography learning about spatial patterns of villages and cities in high schools still faces obstacles in students' understanding of concepts due to teacher-centered learning. This study aims to determine the effect of problem-based learning (PBL) models with the help of Canva media on students' conceptual understanding. Quasi-experimental research was conducted at SMAN 10 Kendari on class XII IPS students. Class XII IPS.1 was designated as an experimental class that learned using problem-based models combined with Canva media, and class XII IPS.2 became a control class with conventional learning methods based on the same abilities. Research data were collected through a concept understanding test and then analyzed using parametric inferential statistical tests. The analysis using independent sample t test after get the normality and homogenity test. The results of the t-test showed a significance value of 0.000, with students in the experimental class having a higher increase in conceptual understanding than those in the control class. This finding shows that PBL utilizing Canva media has proven to be effective in helping students understand the subject matter in problem-oriented learning steps and media that attract students' attention. This study implies that the use of Canva digital media in PBL can be an effective strategy to improve students' conceptual understanding. Teachers are advised to use Canva digital learning media as a teaching aid, especially when implementing PBL, so that students can more easily understand the concepts being studied.